Preservice Elementary School English Teachers' Involvement in Remedial English Education as Their Field Experience: Challenges and Implications - Chin-Wen Chien (Arizona State University, 2015)
This study analyzed 24 pre-service elementary school English teachers design and delivery of remedial education to the fifth and sixth graders in the collaboration between the university pre-service teacher education program and the local elementary school in a city in northwest Taiwan. The pre-service teachers were encouraged by the elementary school fifth and sixth graders improvement in English and their positive attitude toward learning English. However, these pre-service teachers lacked insufficient competence and skills in classroom management, teaching small groups, carrying out class activities, and using the target language. Scheduling of the remedial education as pre-service teachers field experience should be taken into consideration for collaboration between elementary school English teachers and language teacher education programs. A model on the effective collaboration between elementary school English teachers and the language teacher education program is recommended.